The dynamics of portable wealth, social status and competition in the ports, coastal zones and river corridors of northwest Europe, c. AD 650-1100 - Loveluck, Chistopher (Brepols, 2017)
Possession of portable wealth among the connected communities of ports, coasts and river valleys in early medieval northwest Europe reflected a complex web of social relationships of different kinds. It reflected competition in some circumstances, and in others symbiotic lifestyles of relative co-operation, specialisation and advantageous location. For example, the coastal peasantries of northwest Europe seem to have been able to amass significant amounts of portable wealth and imported goods through the trade of products, such as salt. Such trade involved direct contact with foreign mariners, often away from major ports, between the VII and IX centuries. However, there is little evidence of competition with the aristocracy as a result of amassing that wealth. Competition seems to have been focussed on other peasants. Similar, co-operation and maintenance of largely parallel and independent lifestyles is also reflected among the mercantile households of the major emporia ports, between the VII and IX centuries. They enjoyed levels of portable wealth not too different from those of rural landed elites but they did not possess significant landed estates. From the mid X century, however, the portable material culture of the richest merchant-artisans of towns, especially port-cities, shows an affluence to match the lower ranks of the aristocracy, with a range of social practices to match. Hence, by the XI century, there was a trend for active competition between the landed aristocracies and rising merchant patricians.